2014
DOI: 10.1039/c4ra04750h
|View full text |Cite
|
Sign up to set email alerts
|

Edible polyelectrolyte microcapsules with water-soluble cargo assembled in organic phase

Abstract: Using "Generally Recognized as Safe" (GRAS) materials for assembly, edible polyelectrolytes (EPL/PGA) are coated on sugar (maltotriose)–dextran particles and crosslinked (left). Cargo-loaded hollow capsules are created by dissolution of the sugar template (right).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…For example, 3-polylysine and polyglutamic acid are deposited onto water-soluble sugar–cargo mixtures by an organic solvent-based assembly technique and are crosslinked. Cargo-loaded edible microcapsules are created by adding water to dissolve the sacrificial sugar template [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 3-polylysine and polyglutamic acid are deposited onto water-soluble sugar–cargo mixtures by an organic solvent-based assembly technique and are crosslinked. Cargo-loaded edible microcapsules are created by adding water to dissolve the sacrificial sugar template [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This simplifies the encapsulation of watersoluble drugs. Pan et al [182] demonstrated that the application range of capsules obtained by RP-LbL approaches can be expanded, e.g., for the fabrication of edible capsules [183], by controlling different parameters during the assembly of the capsules. Thus, the change in the polyelectrolyte concentration, number of formed layers, nature of the polyelectrolyte, and water fraction used during the assembly allows modulating the thickness of the LbL shell in addition to its density, adhesive properties, and fuzziness.…”
Section: Pre-loadingmentioning
confidence: 99%
“…It is produced by Streptomyces albulus [142] and been approved a food safe holder. Poly-L-lysine have a wide antimicrobial effect on bacteria, fungi [143] and used for encapsulation of food, fish, rice, cooked vegetables [144].…”
Section: Poly-l-lysinementioning
confidence: 99%